Revisiting Bowlby's hypothesis: attachment theory, neuroendocrine maturation and predisposition to psychopathologies (Research, Society and Development, 2020)
Objective: To review the impacts of child stress on the neuroendocrine maturation of the stress response system and the relationships between stress indicators and psychopathologies. Methods: This is a narrative review of literature carried out through a bibliographic survey in books and in the Medline-Pubmed database. The research was carried out without limit of dates using the following keywords: maternal deprivation, psychopathology, maternal care and HPA-axis. Bibliographic Review: With this research, 292 works were found, of these the works were selected to compose this review, classified as works related to the themes: maternal deprivation, attachment and predisposition to psychopathologies. Results: The pioneering laboratory studies on the effects of maternal care date back to the 50s, after that period, many studies were carried out to describe the molecular, neurobiological and behavioral bases of attachment. These studies demonstrate the involvement of cytokines and the HPA-axis in the modulation of attachment. The research carried out shows that the interference in the attachment system between mother and puppies leads to unfavorable changes for the CNS maturation. Conclusion: It is concluded that the maturation of the stress response system is strongly modulated by the quality of the neonatal experience, with close relationships between early stress and predisposition to psychopathologies in adulthood being described.